The lymphocytotoxic effect of homoprobiotic bifidobacteria and lactobacilli autostrains - I. P. Pogorelsky; I. Yu. Chicherin; I. A. Lundovskikh; I. A. Darmov; I. V. Marakulin (Журнал инфектологии)
The results of the experimental studies of the lymphocytotoxic effect of homoprobiotic bidfidobacteria and lactobacilli autostrains on lymphocytes of guinea pigs are presented. Autostrains of homoprobiotic bifidobacteria and lactobacilli isolated from the feces of guinea pigs were used in the experiments. Isolation of the fraction of lymphocytes from the blood of guinea pigs for lymphocytotoxic test was carried out according to the sanitary rules SP 3.3.2.561-96. Intensity of damage in lymphocytes was assessed by counting the points and the cytotoxic index. The experimental results indicate that under the influence of large doses of homoprobiotic bifidobacteria and lactobacilli autostrains cytolysis occurs of only a small number of lymphocytes, and thus, the reaction of lymphocytes with autostrains of homoprobiotic bifidobacteria and lactobacilli is within the physiological range.